PRELIMINARY CORE PREPARATION FOR SPECIAL CORE ANALYSIS-GUIDELINES - Herlan Adim (Scientific Contributions Oil and Gas, 2001)
The application of core analysis to provide data for reservoir evaluation is not a new science but has seen continued research activity over along period. Core analysis is complex containing many stages between the reservoir and the final measurements and interpretation. To ensure the data produced is valid, every step along this phase must be handled with equal attention. Recently developed techniques of measuring certain special core analysis of rock formation are being perfected. The objective of this paper is to provide information that will be of practical value to geologists and engineers involved with preliminary core preparation program. Following is a guideline for preliminary special core preparation. The step by step outline presented below is a suggested guideline and, most certainly, modifications and or changes may be made. However, this guideline has been found to be very successful for laboratory works.